The Effect Of The Poe (Prediction, Observation, Explanation) Learning Model On Results Learning Economics For Grade X Students - Barus, Dila Safira Br; Batubara, Elisabth Margareta; Sinaga, Dearlina (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to determine the effect of the POE (Prediction, Observation, Explanation) learning model on students’ learning outcomes in Economics for Grade X at SMA Swasta Imelda Medan in the 2024/2025 academic year. The study employed a quantitative approach using an experimental method with a pretest-posttest control group design. The research subjects consisted of two classes: class X-B as the experimental group and class X-A as the control group, with a total of 68 students. The research instrument used was a multiple-choice test administered before and after the treatment. The results showed that the average pretest score in the experimental class was 14.85, which increased to 17.24 in the posttest. The average N-Gain score was 0.478 (47.80%), categorized as moderate. The t-test analysis revealed a significance value of 0.000 < 0.05 and a t-value of 8.162, indicating a significant effect of the POE learning model on student learning outcomes. Additionally, the regression test showed a significance value of 0.001 < 0.05, confirming the model's significant influence. The average N-Gain in the control class was only 0.208, showing a lower improvement compared to the experimental class. Thus, it can be concluded that the POE learning model has a positive and significant effect on improving students’ learning outcomes in Economics